Dakwah Maslahah melalui Sertifikasi Halal - Manuputty, Rifqi Firmansyah; Islam, Muhammad Syamsuddinil; Aziz, Moh. Ali (IAIN Padangsidimpuan, 2025)
This study examines the concept of Dakwah Maslahah, an Islamic outreach approach focused on achieving public good (maslahah) and preventing harm (mafsadat), within the context of the urgent need for halal certification for Micro and Small Enterprises (MSEs) in Indonesia. Amid the rapid growth of the global halal industry and the certification mandate under the Halal Product Assurance Law (UU BPJPH), the participation of MSEs continues to face challenges. This research analyzes the conceptual and normative foundations of Dakwah Maslahah, its contextual and transformative characteristics, and its relevance in increasing awareness and encouraging halal certification practices. Although the direct economic impact of halal certification for MSEs is not always immediate, the non-economic benefits, such as increased producer and consumer trust, are significant. The study identifies research gaps in the concrete implementation of Dakwah Maslahah for halal certification, its connection to holistic well-being (falah), its integration into policy, and the challenges faced by da'wah practitioners. It concludes that Dakwah Maslahah has a strategic role in articulating the communal obligation (fardlu kifayah) to provide halal products and in motivating MSEs, in line with the Objectives of Islamic Law (Maqasid al−Shari′ah). It recommends the development of innovative da'wah models, further empirical research, policy refinement, capacity building for da'wah practitioners, and interdisciplinary collaboration to realize the welfare of the community through halal certification.